COMPARISON OF EFFICACY OF LIGHTENING PEEL VERSUS IPL FOR TREATMENT OF EPIDERMAL MELASMA (The Research of Medical Science Review, 2025)
Background: Epidermal melasma remains a therapeutic challenge, with limited real-world data comparing Lightening Peel and IPL. Objective: To evaluate the efficacy and safety of Lightening Peel (glycolic acid 30%) versus Intense Pulsed Light (IPL) in cases of epidermal melasma.Methods: Prospective observational cohort study conducted at the Dermatology Department of CMH Abbottabad, involving 80 patients with epidermal melasma (diagnosed using Wood's lamp). Patients were treated either with Lightening Peel (n=40) or Intense Pulsed Light (IPL) therapy (n=40). Outcomes measured included reduction in MASI score, adverse events, and patient satisfaction at 6 months. Results: Lightening Peel had greater reduction of MASI score (42% vs. 28%, p=0.003), fewer PIH occurrences (5% vs. 18%, p=0.02), and greater rates of satisfaction (78% vs. 55%, p=0.01) compared to IPL.Conclusion: In clinical practice, Lightening Peel might be more effective and better tolerated in epidermal melasma than IPL.